Nepali Painting: Traditional Motifs in Modern Art - B.K., Jyoti Prakash (Journal of Advanced Academic Research, 2017)
Art is mirror of society. Human Civilization developed through art. Philosopher Langinus said that the power of the art is to create sublime to viewers. There is lot of philosophy in art history but still no any conclusion or scientific answer about the art but art is more contemporary due to the globalization and individual expression. In the case of Nepali art, before the "Kirat" and "Lichhabi" period had also some paintings and sculpture. Because of the weak surface we didn’t have any paintings but can know from the petrography of Lichhabi period. In the world the ancient time had been found to be developing from religious and cultural development. It is absolutely relevant to be saying that the Nepali paintings were also the cause of the religious development. The history of the Nepali painting had been developed on religious base from the history to contemporary situation. So the main objective of the research is to find the core relation between traditional and modern painting.